Ciência da Informação e Redes de Colaboração Acadêmica: diálogos, constituição e perspectivas - Letícia Alves Vieira (2009)
The present research had as an accomplished context the information science field in Brazil and the scientific activities of his researchers. It was presented as a problematic for the understanding of the questions related to the organization and dynamic of the field research, the establishment of scientific collaboration nets and configuration ofresearch thematic committed by the researchers as well as its relation with the scientific leadership consolidation. The goal was to characterized, systematize and analyze the collaboration nets in science of information through the scientific production and the dynamic of field diffusion, aiming to comprehend the relations among the thematic of theaccomplished researches; the construction of an agenda of research and the leadership consolidation in the field. So, it has been identified the research themes in CI, the regularity of the scientific production of the field, as well as its working dynamic, in order to characterize the scientific production of the field; the field scientific researchers/leaders have been identified in order to understand the cause of the leadership (intellectual, politic and social aspects); the identification and analysis of the conditions (main and support actor), which ones the Brazilian researchers act in leadership in CI field, it has contributed to the later analysis and identification of net collaborative formation among the Brazilian researchers and the intervenient factors in this formation and the thematic systematization and research dynamics had the final aim of understand if the same reflect a field research agenda. The object of study was the representations of the collaboration academic nets present in the materiality shoed through the periodic literature in science of information in Brazil and in the researchers scientific activities. According to the research classification, it is exploratory and descriptive type, once that aimed to describe and characterize one certain situation inside a specific social context. According to the data analysis and collect, it is aquantitative and qualitative research, because it has worked with data that were statistically analyzed providing the knowledge of the area in study through the accomplished analysis. In order to accomplish the proposed goal, it has been used a method triangulation: bibliometry, semi structured interviews and social nets analysis. The research universe to the bibliometric study was about 468 published articles in a period of time from 2002 to 2007 in the periodic: Science of information, Datagramazero and Science of Information Perspectives. In order to classify the thematic, it was used a taxonomy proposed by Hawkins, Larson e Caton (2003), to the science of information. The aim of the semi structured interviews was the complementation and the better reach in the identification and analysis of the academic leadership aspects in the field. Finally, the semi structured interviews and social nets analysis allowed us the knowledge among the existent interactions among the field researchers. In order to summarize, it has been conclude that science of information, even after 40 years of field institutionalization stillhas the researchs thematic aimed to itself and presents an unequal distribution among the research themes demonstrating an inexistence of a research agenda. The area leadership is pulverized when observed under the politics, social and intellectual aspects. The field does not represent collaboration among the pairs, when it is due to the partnerships in research and products and services development, once there still is the academic collaboration perception only in co-authority activities.